concept BEAUTY, narrative technique, ancient Greek novel, Longus - Оліщук, Роксоляна Леонідівна; Макар, Інеса Степанівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
This article is an attempt to determine the concept BEAUTY in Longus’ novel as a complex by structure and content verbalized concept of human consciousness. As the text analysis of the novel „Daphnis and Chloe” testified the concept BEAUTY is frequently used in connection with such key concept for any culture as HUMAN, because the whole culture concept sphere has anthropocentric character. The findings of present investigation show that the number of noun and adjectival lexemes verbalizes the concept BEAUTY and they are related first of all with the main characters of the novel – Daphnis and Chloe. The author pays attention exclusively to the external beauty of the novel’s characters and to objects of nature. In the Longus’ novel the lexemes of different parts of speech characterize beauty. Among the nouns is τὸ κάλλος which is the dominant and a set of somatic vocabulary combined with epithets denoting beauty. Adjectives-synonyms καλός, ὡραῖος, ἀγαθός, γλαφυρός, εὔμορφος, εὐτρεπής, θαυμάσιος, πάγκαλος may also function as predicates of beauty of different subjects and objects in the novel „Daphnis and Chloe”. Aesthetic epithets demonstrate the author's aspiration to display everything beautiful and almost ideal. Thus, the concept  BEAUTY is an important addition to the generalization and characteristics of the concept system of ancient Greek culture. The research will contribute to deep perception of the national language picture of the world. The results prove that the list of narrative techniques is an important instrument for analysing the concept as a part of both the whole national conceptual system and individual the author’s one.